THE INFLUENCE OF PRICES, SERVICE QUALITY AND PROMOTIONS ON CONSUMER SATISFACTION IN BUYING DIGITAL PRODUCTS AND ACCESSORIES AT THE BE ONE TEMBALANG COUNTER, SEMARANG CIT - Syakur, Abdan; Purwanto, Edy (Economics and Business International Conference Proceeding, 2024)
The population used in this research took the research object at the BE One Cell Tembalang counter and took the counter consumers as subjects. In this research, because the population size is unknown, the sample size uses the Cochran formula. In this research, the primary data used was distributing questionnaires to 100 respondents. Results of research that has been carried out. That the F value calculated from the influence of the variables price (X1), service quality (X2) and promotion (X3) from the results of the F statistical test gets an F value of 0.000. A significance value of less than 0.05 indicates a significant regression model and can be used to predict the consumer satisfaction variable (Y). The results of this research show that price, service quality and promotion simultaneously influence consumer satisfaction.